Spatio-temporal patterns of Holocene environmental change in southern Sicily - Calò, Camilla; Henne, Paul D.; Curry, Brandon; Magny, Michel; Vescovi, Elisa; La Mantia, Tommaso; Pasta, Salvatore; Vannière, Boris; Tinner, Willy (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Few examples of natural forest remain near the Mediterranean coast. Therefore, it is difﬁcult to study how coastal forests respond to climatic change or their resilience to human impact. We developed new sedimentary record of Holocene vegetation and ﬁre history at Lago Preola, a coastal lake in southwestern Sicily (Italy). In order to verify the existence of forest at large scale on the coast, we compare pollen from Lago Preola, a medium-sized lake (33 ha), to Gorgo Basso, a small lake (3 ha) located nearby with the aim of separating local from extra-local vegetation dynamics through time using pollen percentages and inﬂux. We then compare Lago Preola pollen to the record from Biviere di Gela, a large lagoon (120 ha) situated 160 km to the east in southern Sicily, to examine differences in vegetation dynamics between the two coastal areas during the Holocene. Lake-level reconstructions and ostracode analyses from Lago Preola provide vegetation-independent evidence of climate change, and help to disentangle human and climatic impacts on vegetation. Pollen data indicate Pistacia-dominated shrublands replaced open grasslands in the region surrounding Lago Preola by 9500 cal yr BP. This change coincided with rising lake levels and the development of an ostracode fauna typical of fresh waters. Evergreen forest dominated by Quercus ilex and Olea europaea started to expand by 7000 cal BP and consolidated at 6500 cal yr BP, when lake levels were near their Holocene high. Similarities between pollen from Lago Preola and Gorgo Basso demonstrate that forest was the dominant vegetation type in coastal Sicily during the middle Holocene at both regional and local scales, and even developed in the drier climatic setting around Biviere di Gela. Lake levels fell at Lago Preola after 7000 cal yr BP, with a strong decline accompanied by increasing salinity after 4500 cal yr BP. However, no transition in vegetation matched these inferred hydrological changes. Instead, forests persisted in the surrounding region until 2200 cal BP when human disturbance intensiﬁed. We propose that different climatic factors control lake levels and vegetation in coastal Mediterranean ecosystems. Whereas lake levels are most sensitive to the abundance of winter precipitation, coastal forests depend on spring precipitation and are limited by the length of summer drought. Moisture availability remained suitable for evergreen forests in coastal Sicily during the late Holocene, and humans, not a drier climate drove the regional forest decline.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Holocene; Mediterranean; paleoecology; Paleohydrology; Sicily

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J S; Geel, B Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J. S.; Geel, B. Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

CHARCOAL ANALYSIS and the VEGETATIONAL EVOLUTION of NORTH-WEST PORTUGAL - FIGUEIRAL, I. (Oxford Journal of Archaeology, 1993)
Summary: The palaeoenvironment of north-west Portugal is investigated from the late Bronze Age to Roman times. This research is based on the analysis of charcoal from seven archaeological sites. the results contain important information for a better understanding of the vegetational environment of man during this period. Man-environment relations are also examined.
APSAPSThe following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: charcoal; paleoecology; Portugal; vegetational environment

CHARCOAL ANALYSIS and the VEGETATIONAL EVOLUTION of NORTH-WEST PORTUGAL - FIGUEIRAL, I (Oxford Journal of Archaeology, 1993)
Summary: The palaeoenvironment of north-west Portugal is investigated from the late Bronze Age to Roman times. This research is based on the analysis of charcoal from seven archaeological sites. the results contain important information for a better understanding of the vegetational environment of man during this period. Man-environment relations are also examined.
APS
Keywords: charcoal; paleoecology; Portugal; vegetational environment